2020
DOI: 10.3390/su12177169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grazing Types on Community-Weighted Mean Functional Traits and Ecosystem Functions on Inner Mongolian Steppe, China

Abstract: The relationships between community-weighted mean (CWM) functional traits and ecosystem functions have been extensively studied. However, how CWM traits and ecosystem functions respond to grazing types and whether the relationships between CWM traits and ecosystem functions mediate the response of ecosystem functions to grazing types remains controversial. In the present study, we set up a seven-year grazing experiment with four grazing types: no grazing (NG), cattle grazing (CG), sheep grazing (SG), and mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Since grassland productivity is a prominent indicator of vigorous grassland ecosystems and grassland restoration( Schaub et al., 2020 ; Yang et al., 2022a ), evaluating the impact of nutrient-induced variations in community functional structure can inform us of grassland ecosystem functioning. CWM traits and functional diversity have primarily been used to unravel the relationship between functional traits and grassland ecosystem functioning ( Wang et al., 2020 ). We found that CWM traits and functional diversity play a pivotal contrasting role in explaining variations in grassland productivity under nutrient addition ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since grassland productivity is a prominent indicator of vigorous grassland ecosystems and grassland restoration( Schaub et al., 2020 ; Yang et al., 2022a ), evaluating the impact of nutrient-induced variations in community functional structure can inform us of grassland ecosystem functioning. CWM traits and functional diversity have primarily been used to unravel the relationship between functional traits and grassland ecosystem functioning ( Wang et al., 2020 ). We found that CWM traits and functional diversity play a pivotal contrasting role in explaining variations in grassland productivity under nutrient addition ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to natural environmental lter, man-made environment also affects leaf traits such as grazing and grazing exclusion (An and Guoqi 2015;Li et al 2015). In the study of the effect of grazing on leaf traits, it was found that the leaf area and speci c leaf area decreased, and the leaf dry matter content increased under heavy grazing (Wang et al 2016;Wang et al 2020). Meanwhile,we found that different species have different change strategies in different grazing intensity (Bullock et al 2001;Wei et al 2009).…”
Section: Introductionmentioning
confidence: 99%